2014
DOI: 10.1589/jpts.26.1485
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Squat Exercises in Postures for Toilet Use on Blood Flow Velocity of the Leg Vein

Abstract: [Purpose] The purpose of this study was to identify the effects of squat exercises performed in toilet-using postures on the blood flow velocity of the lower extremities for the prevention of deep vein thrombosis. [Subjects] The subjects were 28 students who were attending B University in Cheonan. They were divided into a group of 14 subjects of sitting toilet users and a group of 14 subjects of squat toilet users. [Methods] The subjects performed squat exercises in different toilet-using postures and we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A 2009 guideline for the Diagnosis, Treatment, and Prevention of Pulmonary Thromboembolism and Deep Vein Thrombosis 4 ) states that ankle pumping exercises are effective for the prevention of DVT. However, there has been much debate about the most effective methods 5 ) and modes of ankle pumping exercises 6 ) . Standardized ankle pumping exercises have not been established yet.…”
Section: Introductionmentioning
confidence: 99%
“…A 2009 guideline for the Diagnosis, Treatment, and Prevention of Pulmonary Thromboembolism and Deep Vein Thrombosis 4 ) states that ankle pumping exercises are effective for the prevention of DVT. However, there has been much debate about the most effective methods 5 ) and modes of ankle pumping exercises 6 ) . Standardized ankle pumping exercises have not been established yet.…”
Section: Introductionmentioning
confidence: 99%
“…The DPMD brings the hips and knees in a pseudo-squatting position thus facilitates relaxation of the pelvic oor muscles during defecation [16]. It was also reported that the squatting action during use of squatting toilets improved blood ow velocity in the lower extremities [17], and the user is subjected to squatting, as a form of exercise for strengthening of the quadriceps muscles. Quadriceps strength is associated with a lower cardiovascular mortality in patients with coronary artery disease [18].…”
Section: Resultsmentioning
confidence: 99%
“…The DPMD brings the hips and knees in a pseudo-squatting position thus facilitates relaxation of the pelvic floor muscles during defecation. 16 It was also reported that the squatting action during use of squatting toilets improved blood flow velocity in the lower extremities, 17 and the user is subjected to squatting, as a form of exercise for strengthening of the quadriceps muscles. Quadriceps strength is associated with a lower cardiovascular mortality in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%